Didactic means of overcoming difficulties in the development process of students’ motivation for creative activity - Valentina G. Ryndak; Gulmira S. Saifutdinova; Margarita V. Kozyar (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The research emphasizes the importance of the motivational component in the creative activities of students, notes the correlation of motivational-personal creativity, verbal and non-verbal creativity with academic performance in academic subjects. Difficulties in the development process of students motivation for creative activity were determined, the characteristic of pedagogical prevention, pedagogical diagnostics and pedagogical prevention as the didactic means of preventing and eliminating the difficulties in question was provided. The didactic reasons for students failures in creative activity (independent and relatively dependent on the teacher) are highlighted. Preventive, diagnostic and therapeutic procedures ensuring the elimination of the above-mentioned causes are justified. The reasons of socio-economic and psychological nature affecting the efficiency of students motivation development in creative activity were identified. The results of the teachers readiness to overcome difficulties in the motivation development for students to creative activity are given.